OP0218 Evaluation of The Acr and Slicc Classification Criteria in Juvenile Systemic Lupus Erythematosus: A Longitudinal Analysis. (15th July 2016) - Lythgoe, H.; Morgan, T.; Heaf, E.; Lloyd, O.; Beresford, M.W.; ,
Abstract : Background: Juvenile-onset systemic lupus erythematosus (JSLE) is a severe multi-system inflammatory disease with very varied presentation and disease course. Diverse clinical manifestations means classification of JSLE can prove challenging. The Systemic Lupus International Collaborating Clinics (SLICC) group proposed revised classification criteria for systemic lupus erythematosus (SLICC-2012 criteria) 1 . Objectives: This study aimed to compare the SLICC-2012 criteria with the widely used American College of Rheumatology classification criteria (ACR-1997 criteria) 2.3 in a national cohort of JSLE patients and evaluate how classification criteria that individual patients meet evolved over time. Methods: Data from patients in the UK JSLE Cohort Study with a senior clinician diagnosis of probable, evolving or definite JSLE was reviewed. Patients were classified using both criteria within one year of diagnosis and at latest follow-up (following a minimum twelve month follow-up period). Sensitivity of each classification criteria was compared using McNemar's test. Results: 226 patients were included. The SLICC-2012 was more sensitive than ACR-1997 at diagnosis (92.9% vs 84.1% p<0.0001) and after follow-up (100% vs 92.0% p<0.0001). Figure 1 provides an overview of our results. Of those patients meeting the SLICC-2012 criteria and not the ACR-1997 criteria 59% of patients at diagnosis and 61% of patients at follow-up, scored more than one additional point on the SLICC-2012. In particular, the inclusion of hypocomplementaemia on SLICC-2012 facilitated classification of more patients using these criteria. Conclusions: The SLICC-2012 was better able to classify patients with JSLE than the ACR-1997 and did so at an earlier stage in their disease course. SLICC-2012 should be considered for classification of JSLE patients for the purpose of observational studies and clinical trial eligibility. It may also be useful in daily practice to corroborate clinician diagnosis of JSLE. References: Petri M, Orbai A, Alarcon G, et al. Derivation and validation of the Systemic Lupus International Collaborating Clinics classification criteria for systemic lupus erythematosus. Arthritis Rheum 2012;64:2677–86. Hochberg M. Updating the American college of rheumatology revised criteria for the classification of systemic lupus erythematosus. Arthritis Rheum 1997;40:1725. Tan E, Cohen A, Fries J, et al. The 1982 revised criteria for the classification of systemic lupus erythematosus. Arthritis Rheum 1982;25:1271–7. Acknowledgement: This abstract is written on behalf of the UK JSLE Study Group. We would like to thank all of the patients and their families for participating in this study, and acknowledge the support given by all of the multidisciplinary teams within each paediatric centre. In addition, special recognition is made to LUPUS UK for financially supporting the UK JSLE Study Group. Special recognition also goes to Mrs Carla Roberts for her continued support of the UK JSLE Cohort Study and Mr Duncan Appleby for database and information technology support. Disclosure of Interest: None declared